PERTANGGUNGJAWABAN PIDANA PIHAK SWASTA DALAM TINDAK PIDANA KORUPSI - Bayu Setiawan (Kosmik Hukum, 2011)
In the society, it was formed a mindset that civil servants is the only actor who did corruption criminal act. This born an opinion that corruption criminal subject in Corruption Eradication Act is just applied for civil servants. The cause that forms this perception is due to the usage of civil servants term in some articles in Corruption Eradication Act and most undergoing corruption cases is being led to civil servants or state power as single party involved. But by concerning one example case of loans allocated by Bank Indonesia in the form of Bank Indonesia Bank Liquidity fund (BLBI) which brought state bankruptcy, it's well identified that most actor who committed the crime is someone that come from private sector. Here, private sector in corruption criminal act is defined as the exclusion set of civil servants definition.This research aims to expose: (1) Regulated of corruption articles for private sector by the Corruption Eradication Act (2) Criminal responsibility for private sector with Corruption Eradication Act.Research follows normative law method using secondary data. After compiling all required literatures and reference documents as well, interpretation is made from authentic, grammatical, systematic, and historical aspect, yields two subjects or more and those are used as object to be analyzed, in order to get answers for problem addressed within this research. Research comes out with the result of identifying 14 (fourteen) articles ruling the corruption criminal act that is done by private sector. The articles are categorized into three groups: criminal act of detrimental effect to the finances of the state or the economy of the state, graft criminal act, and dishonesty criminal act and the penalization for crime acted by private sector is death sentence, putting in into jail, paying a fine, and supplementary indictment Key Words: Responsibility and CcrruptionCriminal